1980
DOI: 10.1159/000232658
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies to Collagen in Patients with Chronic Liver Diseases

Abstract: Sera of patients with various liver diseases were investigated for the presence of autoantibodies to type I collagen with a sensitive radioimmunoassay employing 3H-labelled collagen type I. A high percentage (69%) of patients with chronic liver diseases, equally distributed between chronic active hepatitis and alcoholic liver disease, was found to possess antibodies to denaturated type I collagen, while no antibodies against native collagen were found. These antibodies belonged predominantly to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1982
1982
1996
1996

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Based on these findings, it appears that antibodies to denatured collagen may be a common consequence of inflammatory arthritis. Antibodies to denatured collagen have also been described in chronic liver disease (28) and chronic pulmonary disease (10). The antibodies may in fact be a consequence of a variety of conditions in which there is connective tissue inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these findings, it appears that antibodies to denatured collagen may be a common consequence of inflammatory arthritis. Antibodies to denatured collagen have also been described in chronic liver disease (28) and chronic pulmonary disease (10). The antibodies may in fact be a consequence of a variety of conditions in which there is connective tissue inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…This suppression could have been lost when lymphocytes were isolated and cultured in vitro (28,29), allowing the detection of immunologic memory to the autoantigens that had developed after surgery. Autoimmunity to different collagen types has been observed in a number of diseases involving connective tissue destruction (30)(31)(32)(33)(34)(35)(36) and these lesions do not necessarily show immune involvement histologically (34).…”
Section: Discussionmentioning
confidence: 99%
“…Kravis et al have reported that patients with idiopathic pulmonary fibrosis also have cellular reactivity to collagen as measured by production of inigration inhibition factor by cells cultured in the presence of type I collagen [30]. There have also been at least 2 reports of antibodies to denatured type I collagen in chronic liver disease [31,32]. Based on these observation it would be possible to speculate about common pathogenetic mechanisms causing a variety of fibrosing conditions.…”
Section: Collagen Autoimmunity In Other Diseasesmentioning
confidence: 99%